Correlating high temperature thin film ionomer electrode binder properties to hydrogen pump polarization. Issue 13 (18th May 2021) - Venugopalan, Gokul; Bhattacharya, Deepra; Kole, Subarna; Ysidron, Cameron; Angelopoulou, Polyxeni P.; Sakellariou, Georgios; Arges, Christopher G.
Abstract : Influence of ionomer electrode binders thin film properties on electrochemical hydrogen pump (ECHP) polarization. Abstract : Ionomer electrode binders are important materials for polymer electrolyte membrane (PEM) fuel cells and electrolyzers and have a profound impact on cell performance. Herein, we report the effect of two different types of high-temperature (HT) ionomers, characterized as thin films (∼10 nm), on hydrogen oxidation/evolution reaction (HOR/HER) kinetics and hydrogen permeability using interdigitated electrode (IDE) platforms decorated with nanoscale platinum electrocatalysts. The two different ionomers studied were poly(tetraflurostyrene phosphonic acid- co -pentafluorostyrene) (PTFSPA) and quaternary benzyl pyridinium poly(arylene ether sulfone) imbibed with phosphoric acid (QPPSf-H3 PO4 ). The reaction kinetics and limiting current values observed with thin film ionomers on IDEs were commensurate to the values observed in electrochemical hydrogen pumps (ECHPs) that use the ionomers as electrode binders. Using PTFSPA as the binder, an HT-PEM ECHP showed 1 A cm −2 at 55 mV when using 2 mgPt cm −2 in the membrane electrode assembly.